2007
DOI: 10.1002/cmdc.200700022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cruzain Docking, and in vitro Studies of Aryl‐4‐Oxothiazolylhydrazones Against Trypanosoma cruzi

Abstract: Research in recent years has demonstrated that the Trypanosoma cruzi cysteine protease cruzain (TCC) is a valid chemotherapeutic target. Herein we describe a small library of aryl-4-oxothiazolylhydrazones that have been tested in assays against T. cruzi cell cultures. The docking studies carried out suggest that these compounds are potential ligands for the TCC enzyme. The most promising compound of this series, N-(4-oxo-5-ethyl-2'-thiazolin-2-yl)-N'-phenylthio-(Z)-ethylidenehydrazone (6 f), was shown to be ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…The 2-hydrazolyl-4-thiazolidinone-5-carboxylic acid derivatives have shown promising activity on the cruzipain protease [12]. The most promising compound in series of aryl-4-oxothiazolylhydrazones was shown to be very active at non-cytotoxic concentrations in in vitro assays against Trypanosoma cruzi cell cultures and exhibited potency comparable with the reference compounds (IC 50 (Y strain) ¼ 0.3 mM) [9]. Among pyrazoline derivatives, some novel compounds have been identified as inhibitors of the trypanosomal cysteine protease cruzain with IC 50 of 40e230 nM [13].…”
Section: Introductionmentioning
confidence: 99%
“…The 2-hydrazolyl-4-thiazolidinone-5-carboxylic acid derivatives have shown promising activity on the cruzipain protease [12]. The most promising compound in series of aryl-4-oxothiazolylhydrazones was shown to be very active at non-cytotoxic concentrations in in vitro assays against Trypanosoma cruzi cell cultures and exhibited potency comparable with the reference compounds (IC 50 (Y strain) ¼ 0.3 mM) [9]. Among pyrazoline derivatives, some novel compounds have been identified as inhibitors of the trypanosomal cysteine protease cruzain with IC 50 of 40e230 nM [13].…”
Section: Introductionmentioning
confidence: 99%
“…Halogen atoms are added to compounds during drug design to optimize binding affinities, 13 to improve oral absorption and/or to enhance blood-brain barrier (BBB) permeation. 4 A number of studies have shown that one of the reasons for the success of this strategy is the formation of non-bonded interactions referred to as “halogen-bonds.” 5 A halogen bond is a highly directional, non-covalent interaction between a halogen atom and another electronegative atom.…”
Section: Introductionmentioning
confidence: 99%
“…An attempt was then made to synthesize two bioisosteres [16] of 2 b: the semicarbazide 2 a and aminoguanidine 2 c derivatives, in addition to the analogues of 2 b containing N-methyl or N-phenyl substituents. Subsequently, a short series of phthalimides bearing the thiazolin-4-one ring (compounds 3 a-d) was also investigated, for reasons of the bioisosteric relationship present between thiazolin-4-ones and thiosemicarbazones [17] and the significant number of thiazolin-4-ones that are active against multidrug-resistant cancer cells, as in the case of the lead compound 3. [18] Our design incorporated the molecular hybridization approach suggested by the structural features of prototypes 1-3 in addition to molecular bioisosterism (Figure 1).…”
Section: Introductionmentioning
confidence: 99%